The Use of An Interactive Method Called Six Different Headgear in Classes - Soliyev Ilhomjon Sobirovich; Nuriddinova Mohlaroyim Shavkatjon qizi (Periodica Journal, 2023)
In this article, the popularization of the interactive method that can be used in classes, innovative approach to lessons using foreign experiences, its influence on the effectiveness of the lesson, and the ideas that motivate today's pedagogue to approach the lesson process with a modern spirit are included
Keywords: Innovative approach; efficiency; interactive